The effect of defoliation on growth parameters of banana (Musa spp.) - Sedhain, Gopi Krishna; Gartner, J.A.; Upasena, S.H.; Little, David C.; Government of Switzerland (Bangkok : Asian Institute of Technology, 1991)
Two studies of defoliation on bananas (Musa spp.) were carried out to determine the optimum number of leaves on plant required for maximum growth and higher leaf biomass production for feeding ruminant animals in an integrated crop/livestock/fish farming system in rainfed area. In Experiment I, a local Thai triploid variety of banana (Klue Namwa, ABB) s uckers were planted at a plant population of 1333/ha in rows 3m x 2.5m on raised beds in the 2nd week of Nov, 1990. Suckers were irrigated by trickle method 2-3 times/week by polythene pipe throughout the experimental period. Fertilization was done in the forms of Urea, TSP and MOP which supplied about 150g N, 33g P and 100g K/plant (200 kg N, 44 kg P & 133 K kg/ha). Defoliation was done to 4, 5, 6, 7, 8, . 9 and 10 leaves remaining on t he plant. Dates of leaf emission, sucker emergence, and number of leaves/plant and fresh weight of all defoliated leaves were recorded daily throughout the experimental period. DM determination of 1 eaves was done weekly, psudostem height/girth and leaf length/width growth measurements wer e done fortnightly intervals. The leaf e mission rate, average number of first s uckers emergence, pseudostem height and leaf length growth rates and total leaf biomass yield of banana were significant l y different d e tween treatments, whereas, the pseudostem girth and leaf width growth rates and DM content of leaf was not. However, all these parameters observed and measured during experimental period-7 months did not s how a linear correlation with the l eve ls of defoliation of banana. On an average, plants defoliated to 6 and 7 leaves remaining on plants grew better and produced more leaf biomass yield during the dry season. The Experiment II was conducted from 16 January to 31 May, 1991 on the older plants grown on the marginal areas of the AFE farm under rainfed condition. Leaf emission rates on both plants and suckers were comparatively lower throughout the dry season and total leaf biomass yield of banana was also less under the rainfed condition. However, all above mentioned parameters observed and measured on banana plants grown under the rainfed condition were not significantly different between treatments and show no linear correlation with the levels of defoliation. It was concluded that defoliation from 4 to 10 leaves remaining on banana plants did not s how a linear correlation with the levels of defoliation. However, growth performances of banana defoliated to 6-7 leaves on plants was observed better and about 6-7 leaves will be adequate on the 2Klue Namwa3 variety of banana during the early stage of vegetative phase to ensure better plant growth and higher leaf biomass yield.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Sciences
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Defoliation; Banana